Germany on their minds : German Jewish refugees in the United States and their relationships with Germany, 1938-1988 - Schenderlein, Anne C. (Studies in German history ;, 2020)
"Throughout the 1930s and early 1940s, approximately ninety thousand German Jews fled their homeland and settled in the United States, prior to that nation closing its borders to Jewish refugees. And even though many of them wanted little to do with Germany, the circumstances of the Second World War and the postwar era meant that engagement of some kind was unavoidable-whether direct or indirect, initiated within the community itself or by political actors and the broader German public. This book carefully traces these entangled histories on both sides of the Atlantic, demonstrating the remarkable extent to which German Jews and their former fellow citizens helped to shape developments from the Allied war effort to the course of West German democratization"--